Candidate genes for beef quality : allele frequencies in Swedish beef cattle - Leveau, Carina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2008)
In Swedish beef retail cuts there are marked differences in meat quality, e.g. tenderness and marbling, between individual animals. A proportion of these differences are explained by the animals' genetic make up. A number of polymorphisms in key genes have been reported for their association with meat quality traits and the major candidate genes in this paper are DGAT1, Leptin, TG, CAPN1, CAST, and DNAJA1. Genotype information on 400 individuals from five Swedish beef breeds (Charolais, Hereford, Angus, Simmental and Limousin) regarding eight polymorphisms located in four candidate genes was compared to literature reports. The results from frequency analyses of these eight polymorphisms revealed only minor deviations from previous reports. However, the Simmental individuals in this study differed from both the other Bos Taurus breeds included in the study and from results in the literature in that a lower frequency of the "tender" T allele was observed for the marker CAPN1-4571 in the gene encoding the proteolytic enzyme calpain. This could be a result of "sampling effect" due to small sample size i.e. the samples are not representative for the overall population.